2019
DOI: 10.1128/aem.02083-18
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Signaling via the TORC1-Greatwall-PP2A B55δ Pathway Is Responsible for the High Initial Rates of Alcoholic Fermentation in Sake Yeast Strains of Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae sake yeast strain Kyokai no. 7 (K7) and its relatives carry a homozygous loss-of-function mutation in the RIM15 gene, which encodes a Greatwall family protein kinase. Disruption of RIM15 in nonsake yeast strains leads to improved alcoholic fermentation, indicating that the defect in Rim15p is associated with the enhanced fermentation performance of sake yeast cells. In order to understand how Rim15p mediates fermentation control, we here focused on target-of-rapamycin protein kinase co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…However, reduced viability due to deletion of rim15 may be desirable in some cases. Recent comparative genomic investigations revealed that RIM15 plays a role in controlling alcoholic fermentation [36]. Deletion of rim15 significantly increased the fermentation rate and shortened the fermentation period [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reduced viability due to deletion of rim15 may be desirable in some cases. Recent comparative genomic investigations revealed that RIM15 plays a role in controlling alcoholic fermentation [36]. Deletion of rim15 significantly increased the fermentation rate and shortened the fermentation period [37].…”
Section: Introductionmentioning
confidence: 99%
“…The activated IGOs can transmit signals to downstream effectors by inhibition PP2A [43]. The orthologues pathway has also been found in Schizosaccharomyces pombe , and this pathway plays a pivotal role in carbohydrate metabolism [36]. Despite the advances made in those studies, the mechanism of how the STK-12 pathway affects cellulase production has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Upstream of TORC1, the adenosine monophosphate kinase AMPK has been proposed to mediate the response to nitrogen starvation, and intriguingly, the two complexes can inhibit each other (Davie, Forte, and Petersen 2015; Ling et al 2020). Downstream, the TORC1 pathway is a key regulator of the balance between the stress and growth modules (López-Maury, Marguerat, and Bähler 2008; Rallis, Codlin, and Bähler 2013; Rallis et al 2014), with targets including eukaryotic initiation factor 2 subunit alpha (eIF2α) (Valbuena, Rozalén, and Moreno 2012), the SAGA complex (Laboucarié et al 2017), and the rate of fermentation through Greatwall and PP2A B55δ (Watanabe et al 2019). These questions are often studied during adaptation to changing conditions and our system using continuous culture in turbidostats provides an attractive set up for future studies of the mechanisms that maintain the stress vs growth gene expression balance in steady-state conditions.…”
Section: Discussionmentioning
confidence: 99%
“…stress and growth modules(López-Maury, Marguerat, and Bähler 2008;Rallis, Codlin, and Bähler 2013;Rallis et al 2014), with targets including eukaryotic initiation factor 2 subunit alpha (eIF2α)(Valbuena, Rozalén, and Moreno 2012), the SAGA complex(Laboucarié et al 2017), and the rate of fermentation through Greatwall and PP2A B55δ(Watanabe et al 2019).…”
mentioning
confidence: 99%
“…Interestingly, deletion of the CDC55 gene suppresses the phenotype of high fermentation in a RIM15 deletion mutant [103].…”
Section: The Greatwall-endosulfine-pp2a/b55 Pathway Is Required For Gmentioning
confidence: 99%